METABOLISM AND EXCRETION OF ERLOTINIB, A SMALL MOLECULE INHIBITOR OF EPIDERMAL GROWTH FACTOR RECEPTOR TYROSINE KINASE, IN HEALTHY MALE VOLUNTEERS - Ling, Jie; Johnson, Kim A.; Miao, Zhuang; Rakhit, Ashok; Pantze, Michael P.; Hamilton, Marta; Lum, Bert L.; Prakash, Chandra (Drug metabolism and disposition, 2006)
Metabolism and excretion of erlotinib, an orally active inhibitor of epidermal growth factor receptor tyrosine kinase, were studied in healthy male volunteers after a single oral dose of [14C]erlotinib hydrochloride (100-mg free base equivalent, ∼91 μCi/subject). The mass balance was achieved with ∼91% of the administered dose recovered in urine and feces. The majority of the total administered radioactivity was excreted in feces (83 ± 6.8%), and only a low percentage of the dose was recovered in urine (8.1 ± 2.8%). Only less than 2% of what was recovered in humans was unchanged erlotinib, which demonstrates that erlotinib is eliminated predominantly by metabolism. In plasma, unchanged erlotinib represented the major circulating component, with the pharmacologically active metabolite M14 accounting for ∼5% of the total circulating radioactivity. Three major biotransformation pathways of erlotinib are O-demethylation of the side chains followed by oxidation to a carboxylic acid, M11 (29.4% of dose); oxidation of the acetylene moiety to a carboxylic acid, M6 (21.0%); and hydroxylation of the aromatic ring to M16 (9.6%). In addition, O-demethylation of M6 to M2, O-demethylation of the side chains to M13 and M14, and conjugation of the oxidative metabolites with glucuronic acid (M3, M8, and M18) and sulfuric acid (M9) play a minor role in the metabolism of erlotinib. The identified metabolites accounted for >90% of the total radioactivity recovered in urine and feces. The metabolites observed in humans were similar to those found in the toxicity species, rats and dogs.